Dialog Adat dan Agama, Melampaui Dominasi dan Akomodasi (Muslim Hatuhaha di Pulau Haruku Maluku Tengah) - Yance Z. Rumahuru (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2012)
The dialog between local culture and religion cannot be separated with the history of religious communities in Indonesia. This article is aimed to describe a form of dialogue between local culture and religion among Muslims of Hatuhaha community in the Central Moluccas. It is particularly to understand forms of dialogue between local culture and religion, specifically Islam in Indonesia. This article is based on a field research in the Haruku island of Central Moluccas in 2009 by using qualitative method. It has been found that, firstly, there has a constructive dialogue between Islam as a religion and local culture since the religion was accepted as a â€œnew ideologyâ€ within island communities in Indonesia. Secondly, there are three models of dialogue between the religion and local culture, i.e. â€œdominationâ€, â€œaccommodationâ€, and â€œcontextualâ€.